Efficient iterative receiver for LDPC coded wireless IPTV system - YouZhe Fan; She, James; Chi-ying Tsui (2011 18th IEEE International Conference on Image Processing, 2011)
Multi-level superposition coded modulation (SCM) is a scalable technique for wireless video broadcast/ multicast, in which iterative turbo structures provide receivers with multi-resolution demodulations subject to a high complexity. Forward error correction using low-density parity-check (LDPC) code is helpful for better received video quality but further increasing the receiver complexity. In this paper, a method is proposed to reduce the receiver complexity by using a sequential structure with a faster convergence for demodulation. In addition, the iterative demodulator and the LDPC decoder are jointly designed as a multi-loop iterative structure to reduce the decoding complexity. Experimental results show that up to 67% decoding complexity is reduced and better video quality is achieved at receivers under low signal-to-noise ratios.